PRAGMATIC ASPECTS OF ASSERTIVE SPEECH ACTS IN LINGUISTICS RESEARCH ARTICLES - Rakhmatova Farangiz (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
Assertive speech acts constitute the most pervasive illocutionary category in academic writing, yet their pragmatic dimensions remain undertheorised in the existing literature. This article examines how assertive speech acts are pragmatically realised in linguistics research articles, with particular attention to the strategies writers employ to negotiate certainty, manage interpersonal relations, and position themselves within their disciplinary communities. Drawing on Searle's (1969) speech act taxonomy, Hyland's (2005) metadiscourse framework, and Leech's (1983) politeness principles, the article argues that assertives in academic writing are rarely straightforward truth claims — they are carefully calibrated communicative acts shaped by disciplinary norms, audience awareness, and rhetorical purpose. The analysis reveals that hedging, boosting, and indirect assertion are the primary pragmatic strategies through which academic writers modulate the illocutionary force of their assertive acts. The findings contribute to a more nuanced understanding of how assertives function as pragmatic tools for knowledge construction and scholarly positioning in academic discourse.